Effects of Biochemical Alteration in Animal Model after Short-Term Exposure of Jatropha curcas (Linn) Leaf Extract - Osamuyimen O. Igbinosa; Efosa F. Oviasogie; Etinosa O. Igbinosa; Otibhor Igene; Isoken H. Igbinosa; Omoruyi G. Idemudia (The Scientific World Journal)
This study aims to evaluate potential toxic effect of Jatropha curcas leaves methanol extract on laboratory rats as well as determine its LD50. A total of 80 male Wistar rats were used as the experimental animals, 40 for LD50 determination and the other 40 for toxicity study. Based on the pretest that was done in order to establish a range of toxicity, 4 dosages (86.00, 58.00, 46.00, and 34.0 kg/body weight) were chosen. The rats were randomly assigned into four groups with 10 rats in each group. Rats in groups 1, 2, 3, and 4 were given 0 mg/kg, 500 mg/kg, 1000 mg/kg, and 2000 mg/kg body weight of Jatropha curcas extract, respectively, by oral intubation for 21 days. Thereafter, clinical signs, change in body weight, toxicity symptoms, and biochemical parameters were obtained. The LD50 at 95% confidence limits for rats was 46.0 mg/kg body weight (44.95–52.69 mg/kg body mass). There was no clinical and biochemical signs of toxicity when the extract was administered at 500, 1000, and 2000 mg/kg body weight, respectively (P>0.05). Results obtained from this study suggest that liver, kidney, and haematological system of rats tolerated methanolic leave extract of Jatropha curcas at a certain concentration.